PENERAPAN PEMBELAJARAN BERBASIS STEM UNTUK MENINGKATKAN LITERASI SAINS SISWA KELAS V SEKOLAH DASAR PADA MATERI BERKENALAN DENGAN BUMI - Tri Fadillah; Vania agustin; Neni Hermita; Rifqa Gusmida Syahrun Barokah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Scientific literacy is a basic skill that students need to have to face the challengesof the 21st century. This study aims to analyze the improvement of scientific literacyof fifth-grade elementary school students through the implementation of Science,Technology, Engineering, and Mathematics (STEM)-based learning on the topic